A Comparison of Marine Pilots' Planning and Manoeuvring Skills: Uncovering Mental Models to Assess Shiphandling and Explore Expertise. (September 2015) - Orlandi, Luca; Brooks, Benjamin; Bowles, Marcus
<x content-type="archive" xml:space="preserve">Abstract</x> This paper introduces an assessment methodology that can underpin the objective measurement of shiphandling skills and permit comparative analysis of manoeuvring plans against their execution in a full mission bridge simulator. It was hypothesised that expert shiphandlers would have shown a strong consistency between the initial plan provided and the following execution. Ten marine pilots participated in the study. Their performance was evaluated across several variables using data gathered during the planning and objective measurements completed during the execution on a simulator. A significant capability to match execution against the plan was evidenced by the group of pilots. The mathematical analysis proposed represents an objective approach that can assure a valid and reliable assessment when applied across different contexts and needs such as: selection, training and certification of pilots, port development, optimisation of bridge procedures and improvement of equipment design.